Fiber-optic realization of anisotropic depolarizing quantum channels - Karpinski, M; Radzewicz, C; Banaszek, K (Optical Society of American (OSA), 2008)
We employed an electrically driven polarization controller to implement anisotropic depolarizing quantum channels for the polarization state of single photons. The channels were characterized by means of ancilla-assisted quantum process tomography using polarization-entangled photons generated in the process of spontaneous parametric downconversion. The demonstrated depolarization method offers good repeatability, low cost, and compatibility with fiber-optic setups. It does not perturb the modal structure of single photons, and therefore can be used to verify experimentally protocols for managing decoherence effects based on multiphoton interference. © 2008 Optical Society of America.